Full ITS (ITS1-5.8-ITS2) sequences of seven fungal strains in the study: Differences in mycelial turnover and persistence of wood decay fungi at the microscale - Floudas, Dimitrios; Aleklett, Kristin; van Bokhoven, Roos-Marie (Lund University, 2025)
Despite growing knowledge of fungal contributions to decomposition and soil carbon cycles, surprisingly little is known about the turnover of mycelia: what happens to fungal hyphae over time, and how this impacts different fungi’s contribution to carbon sequestration. We compared micro-scale persistence of fungal hyphae using microfluidic chip technology and visual quantification of hyphal degradation and turnover across six different wood-decay Basidiomycete species. The mycelial traits we measured included hyphal extension, coverage, and turnover rates as well as changes in hyphal morphology over time when supplied with two carbon sources of differing recalcitrance.

The dataset included here contains the generated ITS sequences of the seven strains used for molecular identification.
Keywords: Terrestrial ecology; Soil biology; Microbial ecology; Mycology; Ecological physiology; Medical and Health Sciences; Medicin och hälsovetenskap; Ecology; Ekologi